Lietuvių visuomenės ir spaudos veikėjas Adomas Jakštas-Dambrauskas (1860-1938) - Stonienė, Vanda (Knygotyra, 2024)
The article deals with the cultural activities of A. Jakštas-Dambrauskas, one of the most prominent Lithuanian personalities at the end of the 19th century and during the first three decades of the 20th century. While still in secondary school, A. Dambrauskas became known as a Lithuanian patriot. As a Catholic priest and public figure, he never accommodated himself to Tsarist policy; he encouraged the Lithuanian youth and priesthood to resist the Tsarist ban on the Lithuanian press and to fight for the right to teach children in the Lithuanian language (for such resistance, he was banished by Russian authorities from his native country for some years).From 1902 to 1906, he worked at the Spiritual Academy in St. Petersburg. He soon returned to Lithuania and began directing the Society of St. Casimir, which focused heavily on publishing books, periodicals, and newspapers. He directed the activities of the Society for almost three decades; in fact, he worked there up until his death. Many publications of the Society were initiated and prepared by him, and many of his own writings appeared as the Society's publications.A. Jakštas-Dambrauskas' activities were not only restricted to his work at the Society of St. Casimir. His plans and efforts also extended to other fields of Lithuanian cultural life. For more than 50 years, he worked intensively as a publisher, editor, organizer of Lithuanian periodicals, literary figure, publicist, and researcher. A considerable part of his works addressed problems related to religion, philosophy, art, logic, etc. He was well-known for his numerous reviews of Lithuanian poetry and prose works. As a writer, he published several collections of literary pieces. Among his literary achievements, his biographies of many Lithuanian cultural figures and writers should also be mentioned. He was the first to publish scientific and literary texts in Esperanto in Lithuania (from 1922 to 1926, he edited the newspaper Litava Stelo in this language).